2018
DOI: 10.3892/or.2018.6459
|View full text |Cite
|
Sign up to set email alerts
|

RAD52 motif‑containing protein�1 promotes non‑small cell lung cancer cell proliferation and survival via cell cycle regulation

Abstract: DNA repair proteins such as RAD52 have been implicated in tumor progression and response to chemotherapy. RAD52 motif‑containing protein 1 (RDM1) has been implicated in the response to chemotherapeutic agent cisplatin; however, its function in lung cancer progression remains unclear. This study aimed to investigate the role of RDM1 in the progression of non‑small cell lung cancer (NSCLC). We found elevated RDM1 mRNA and protein expression in NSCLC tissues and cell lines compared to levels in normal lung cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…In this study, we identified a novel oncogene, RDM1, mediating the progression of NB, supporting the role of RDM1 in cell proliferation and tumorigenesis. Since DNA repair protein RAD52 has previously been implicated in the development of resistance to cancer therapy [22], RDM1 was initially indicated to have a similar function to RAD52 in DNA repair pathways [16]. Our Oncomine-based (TCGA database) expression analyses and IHC staining in clinical tumor samples confirmed that RDM1 was high expressed.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In this study, we identified a novel oncogene, RDM1, mediating the progression of NB, supporting the role of RDM1 in cell proliferation and tumorigenesis. Since DNA repair protein RAD52 has previously been implicated in the development of resistance to cancer therapy [22], RDM1 was initially indicated to have a similar function to RAD52 in DNA repair pathways [16]. Our Oncomine-based (TCGA database) expression analyses and IHC staining in clinical tumor samples confirmed that RDM1 was high expressed.…”
Section: Discussionsupporting
confidence: 61%
“…Previous work showed the regulation of RDM1 in lung cancer [16] and papillary thyroid carcinoma [17]. However, in this study, we identified RDM1 as an oncogenic target in NB.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…RDM1 −/− cells have been reported to exhibit increased sensitivity to cisplatin . Recently, two different research groups have shown that RDM1 exhibits significant up‐regulation in human lung adenocarcinoma . Accordingly, RDM1 and RAD52 have been proposed to share similar functions in both homologous recombination as well as DNA double‐strand break repair.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, two different research groups have shown that RDM1 exhibits significant up-regulation in human lung adenocarcinoma. 10,11 Accordingly, RDM1 and RAD52 have been proposed to share similar functions in both homologous recombination as well as DNA double-strand break repair. Notably, RDM1 can regulate p53/ RAD51/RAD52, and its down-regulation of p53 is involved in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%